Cardiovascular disease: statistical registration principles and international comparability - I. V. Samorodskaya (Кардиоваскулярная терапия и профилактика, 2009)
The article discusses the principles of calculating cardiovascular morbidity and prevalence indices in the Russian  Federation and USA. The factors influencing significant international differences and affecting the comparability  of cardiovascular statistics across countries, are examined.